The histopathological and molecular heterogeneity of hepatocellular carcinoma: a narrative review - Wonju Chung; Haeryoung Kim (The Ewha Medical Journal)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related deaths worldwide, with poor clinical outcomes due to challenges in early detection and limited efficacy of current treatments such as receptor tyrosine kinase inhibitors and immunotherapy. HCC exhibits significant heterogeneity at both histopathological and molecular levels, complicating its management but offering potential for personalized therapeutic approaches. This review outlines the morpho-molecular heterogeneity of HCC and summarizes various histological subtypes, including steatohepatitic, clear cell, macrotrabecular-massive, scirrhous, lymphocyte-rich, and fibrolamellar HCCs. Each subtype possesses distinct clinical, histological, and molecular features; for instance, steatohepatitic HCC is associated with metabolic dysfunction and shows IL-6/JAK/STAT activation, while clear cell HCCs often have IDH1 mutations and favorable prognosis. The macrotrabecular-massive subtype is linked to poor outcomes and TP53 mutations, whereas scirrhous HCCs express stemness markers and have TSC1/TSC2 mutations. Lymphocyte-rich HCCs are characterized by immune cell infiltration and better prognosis. CTNNB1-mutated HCCs show specific morphological features and may benefit from targeted therapies. Understanding these subtypes and associated molecular alterations is crucial for developing effective diagnostic and therapeutic strategies, including potential predictive biomarkers and personalized treatments. Additionally, the identification of patterns like vessels-encapsulating-tumor-clusters offers prognostic implications and may guide therapeutic decisions. Recent molecular studies have enhanced our comprehension of HCC heterogeneity, laying the groundwork for more personalized approaches. Pathologists play a vital role in recognizing these subtypes, aiding in prognosis prediction and treatment planning. Advances in digital pathology and artificial intelligence may further facilitate biomarker research, ultimately improving patient outcomes in HCC management.